Endobronchial Ultrasound: An Atlas and Practical Guide - Herth, Felix; Ernst, Armin (Springer-Verlag New York, 2009)
Endobronchial ultrasound has received explosive attention amongst pulmonologists, thoracic surgeons and gastroenterologists and the procedure is increasingly being performed. Even though the technology has been in use for over 10 years, technical modifications have just recently lead to the ability for near ubiquitous use. The editors and contributors have all been active in the field for years, are well published and certainly are considered opinion leaders and well-traveled teachers, having offered many courses in bronchoscopy and endobronchial ultrasound.
Includes bibliographical references and index
Keywords: Atlas